NEW APPROACHES IN INVESTMENT RISK MANAGEMENT IN PUBLIC SECTOR IN THE POST-CRISIS PERIOD: A CASE STUDY OF THE REPUBLIC OF SERBIA - Cvetkov, Milan (Poslovna ekonomija, 2021)
The subject of the research in this paper is giving an overview, description and analysis of the new approach in risk management of public sector investment, with a special focus on the Republic of Serbia as a domestic economy. The crisis of 2008 resulted, among other things, in an overall abandonment of neoliberal approach to market, and a complete redefining of market relationships, place and role and significance of particular participants in market. These new market circumstances have in particular affected the market position of public sector along with its market performance. Therefore the main goal of this research in this paper is getting new knowledge, which can be validated in practice, about new approaches to management of public sector investment risks in post-crisis period, with a special focus on the Republic of Serbia and its public sector. The results of the research should provide new knowledge on modalities and effects of new approaches in management of public sector investment risks in the post–crisis period, thus enabling an effective and efficient repositioning of the place, role and significance of the public sector on the market of the Republic of Serbia. In this way they will be useful to the academic community in broadening the scientific data base in this area of interest, as well as policymakers in the process of defining and implementing of public sector policies.
Keywords: Public sector, risk management, investments, post-crisis period, Republic of Serbia.